Retention Behaviour of Weakly Ionizable Acidic Compounds in Ion-Suppression Reverse-Phase Liquid Chromatography with Ternary Mobile Phase - Cao, X.W.; Ming, X.; Wei, Y.N.; Liu, C.C.; Han, S.Y.; Chen, F.Y.; Lian, H.Z.; Ge, X. (Asian Journal of Chemistry, 2012)
Ternary elution system employing organic modifiers, water and simple acid solutions has been widely applied to suppress the ionization of weakly ionizable acidic analytes in reversed-phase liquid chromatography. This paper focuses on the retention behaviour of benzoic acid derivatives using acetic acid or perchloric acid as ion-suppression in such ternary mobile phase. The apparent n-octanol-water partition coefficient (Kow'') was proposed to calibrate the n-octanol-water partition coefficient (Kow) of weak acidic compounds. Consistent with binary mobile phase, log Kow'' was found to have a better linear correlation with log kw, the logarithm of the retention factor obtained by extrapolating to neat aqueous fraction of the mobile phase. This straightforward relationship offers a potential medium for direct measurement of Kow data of weak acidic analytes and can be used to predict retention behaviour of these compounds in the ion-suppression reversed-phase liquid chromatography mode with ternary mobile phase.